Implementation Policy to Development Energy Renewable in the Transition Era Energy - Fatma Ulfatun Najicha; Waluyo Waluyo (International Forum of Researchers and Lecturers, 2024)
Indonesia is still heavily dependent on fossil fuels, particularly coal and petroleum. With declining oil reserves, Indonesia is faced with an energy shortage by 2046, prompting the need for alternative solutions. However, suboptimal regulations can be an obstacle to the maximum utilization of renewable energy potential. Renewable energy is considered vital not only as an alternative to fossil energy but also as a strategic measure to maintain long-term energy supply security. Although Indonesia has large renewable energy potential, such as geothermal, wind, and solar, its utilization is still limited and not optimal. Regulations, including Presidential Regulation No. 112 of 2022, reflects the government's commitment to expand the use of renewable energy. This research uses a normative legal research method with a literature study approach. Secondary data used includes primary legal materials, secondary legal materials, and non-legal materials. Data analysis is carried out qualitatively and presented descriptively. In the discussion, the article discusses the potential of renewable energy in Indonesia, involving resources such as water, solar, wind, geothermal, and bioenergy. Regulations related to renewable energy in Indonesia are explained, including Government Regulation No. 79/2014 on National Energy Policy. There is a strong commitment from various parties, such as Commission VII of the House of Representatives, to support the development of renewable energy. The important role of regulations and policies in supporting the development of renewable energy in Indonesia. This energy transition is key to protecting natural resources, improving general welfare, and educating the nation's life, according to the objectives of the State of Indonesia as stated in the Preamble of the 1945 Constitution.